OUR EXPERIENCE OF SURGERIES IN COVID-19 PATIENTS AT PEMH RAWALPINDI - Gulrez, Amna; Sharif, Asjad; Saqib Khan, Najm Us; Mehboob, Saira (Pakistan Armed Forces Medical Journal, 2020)
The pandemic of COVID-19 corona virus is the most deadly and frightening situation of our times and it is the greatest challenge to which whole world is exposed. However different countries are facing this challenge with different severity and outcomes. We are fighting this pandemic since February 2020 and up till now there is increased surge of cases. PEMH has been declared as corona special hospital and all the entitled cases that are corona positive and need surgeries are being operated here. Elective surgeries have been postponed till resolution of COVID-19 and only emergency surgeries are being carried out in PEMH OT. Special protocols and rules have been designed by hospital management and consultants of different specialties to minimize the risk of cross contamination. This includes minimum number of staff to be exposed in OT, proper donning and doffing of PPE, careful shifting of patient to and from OT, special preparation of operating room before arrival of patient, classified and experienced anesthetist to conduct anaesthesia, preference of regional anaesthesia over general anaesthesia, use of proper disinfectant for surfaces, air and instruments used during surgery, regular screening of staff exposed and even counseling of staff who are psychologically disturbed due to deadliest and negative outcomes of the disease. All of these measures and protocols have been observed to be very useful in infection control and prevention.